Penerapan model problem based learning berbantuan VBA for excel untuk meningkatkan kemampuan penalaran matematis siswa SMP kelas VII - Umini, Umini; Fitriani, Nelly; Nurfauziah, Puji (IKIP Siliwangi, 2025)
This research aims to analyze and examine the improvement of seventh-grade junior high school students’ mathematical reasoning abilities using the problem-based learning model assisted by VBA for Excel, compared to the conventional learning model. The research method used is an experimental method with a quasi-experimental design, consisting of two groups, the experimental class and the control class. This research was conducted at SMP Negeri 2 Batujajar, with the sample comprising of class VII-D as the experimental class and class VII-B as the control class, each with 29 students. The instruments and learning materials used include a mathematical reasoning ability test and student worksheets (LKPD) containing material on plane figures according to the stages of problem-based learning. The data obtained will be analyzed using inferential statistics. The results of this research indicate that the improvement in students’ mathematical reasoning abilities using the problem-based learning model assisted by VBA for excel is better than that of those using conventional learning.